Dynamics of short-term ecosystem carbon fluxes induced by precipitation events in a semiarid grassland - J. Delgado-Balbuena; H. W. Loescher; H. W. Loescher; C. A. Aguirre-Gutiérrez; T. Alfaro-Reyna; L. F. Pineda-Martínez; R. Vargas; T. Arredondo (Biogeosciences, 2023)
Infrequent and small precipitation (PPT) events characterize PPT patterns in semiarid grasslands; however, plants and soil microorganisms are adapted to use the unpredictable small pulses of water. Several studies have shown short-term responses of carbon and nitrogen mineralization rates (called the “priming effect” or the Birch effect) stimulated by wet–dry cycles; however, dynamics, drivers, and the contribution of the priming effect to the annual C balance are poorly understood. Thus, we analyzed 6 years of continuous net ecosystem exchange measurements to evaluate the effect of the PPT periodicity and magnitude of individual PPT events on the daily/annual net ecosystem C exchange (NEE) in a semiarid grassland. We included the period between PPT events, previous daytime NEE rate, and previous soil moisture content as the main drivers of the priming effect. Ecosystem respiration (ER) responded within a few hours following a PPT event, whereas it took 5–9 d for gross ecosystem exchange (GEE; where −NEE = GEE + ER) to respond. Precipitation events as low as 0.25 mm increased ER, but cumulative PPT > 40 mm infiltrating deep into the soil profile stimulated GEE. Overall, ER fluxes following PPT events were related to the change in soil water content at shallow depth and previous soil conditions (e.g., previous NEE rate, previous soil water content) and the size of the stimulus (e.g., PPT event size). Carbon effluxes from the priming effect accounted for less than 5 % of ecosystem respiration but were significantly high with respect to the carbon balance. In the long term, changes in PPT regimes to more intense and less frequent PPT events, as expected due to the effects of climate change, could convert the semiarid grassland from a small C sink to a C source.